Analysis of Elements of Financial Statements Contribution in Cash Wealth Maximization - طلال محمد علي الججاوي; طه سعد كمال آل بكر (Iraqi Journal for Administrative Sciences, 2024)
Each element of financial statements affects in cash inflows and outflows of Corporation and as a result influence on cash wealth maximization (CWM), which is the most important object for Corporations if they want to stay and continue. The aim of the research is to identify contribution elements of financial statements in CWM in the Iraqi shareholding Corporations listed in the Iraqi Stock Exchange (ISX). The results showed that majority Corporations in research sample contrast in elements of their financial statements in the degree of their contribution to CWM and this is due to the improper distribution of cash wealth on these elements and , as a result, continued maximization is not possible. Corporations should distribute cash in such a way as to ensure that they continue to maximize their cash wealth by focusing on elements that contribute to it